Quaternary ammonium salt-attapulgite modified epoxy acrylic resin and preparation method thereof
By adding quaternary ammonium salt and concave and concave rod soil to epoxy acrylic resin, multi-step reaction modification is carried out, and the problem of insufficient corrosion and mechanical properties of existing coatings is solved, achieving high-performance corrosion and mechanical properties improvement.
Patent Information
- Application Number
- CN202411807634.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing epoxy resin coatings have shortcomings in corrosion resistance and mechanical properties, and the large amount of solvents used is not conducive to green development.
By adding quaternary ammonium salt and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and
It significantly improves the corrosion resistance and mechanical properties of the paint, forms a stable protective film, prevents metal corrosion, and improves the acid and alkali resistance and hydrophobicity of the paint.
Smart Images

Figure CN119432198A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a quaternary ammonium salt-attapulgite modified epoxy acrylic resin and a preparation method thereof. Background Art
[0002] In many industries, it is very difficult to replace the metal to be protected from corrosion. Among them, anti-corrosion through coating is a common and widely used green scientific method. The coating is based on the fact that when the metal corrodes, it is chemically inert to the metal corrosive medium, thereby inhibiting the occurrence of electrochemical and chemical reactions, thereby achieving the purpose of corrosion protection.
[0003] Chinese patent CN1375533A proposes to use polyphenylene sulfide modified epoxy resin anticorrosive coating, which has excellent anticorrosion performance, but the amount of solvent added is large, which is not conducive to green development, and there is no research on the mechanical properties of the coating. The inorganic nanoparticle attapulgite added in the present invention has the characteristics of wide source and low price, and at the same time has a great improvement on the mechanical properties of the substrate, and has strong chemical corrosion resistance. By adding imidazoline quaternary ammonium salt corrosion inhibitor, the substrate is modified, which can effectively improve the corrosion resistance of the substrate. The use of a mixed matrix of epoxy resin and acrylic resin effectively avoids the shortcomings of a single epoxy resin that is easy to age and has poor weather resistance. The epoxy acrylic resin coating obtained after mixing has excellent performance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a quaternary ammonium salt-attapulgite modified epoxy acrylic resin and a preparation method thereof, thereby improving the anti-corrosion performance and mechanical properties of the epoxy acrylic resin coating.
[0005] To achieve the above object, the present invention provides the following technical solution: a quaternary ammonium salt-attapulgite modified epoxy acrylic resin, the quaternary ammonium salt-attapulgite modified epoxy acrylic resin and the preparation method are as follows: (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane into a reaction container, performing ultrasonic dispersion, reacting at 80-100° C. for 5-8 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) adding ethanol solvent and amino-modified attapulgite into a reaction container, and after ultrasonic dispersion, adding undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, stirring, and reacting. After the reaction is completed, filtering, washing with ethanol and deionized water, and drying to obtain undecane carboxyl-modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine into a reaction vessel, stirring, heating under reflux, pre-reacting at 130-150° C., reacting for 2-3 hours, raising the temperature, reacting at 180-220° C., reacting for 6-10 hours, ending the reaction, and rotary evaporating to obtain imidazoline grafted attapulgite; (4) adding ethanol solvent and imidazoline-grafted attapulgite into a reaction container, uniformly dispersing by ultrasonication, adding benzyl chloride, stirring, reacting, and after the reaction is completed, performing vacuum distillation, and performing recrystallization with a mixed solution of ethanol and acetone to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir and react in a nitrogen atmosphere, and after the reaction is completed, add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane, mix well, cool, and adjust the pH to obtain a quaternary ammonium salt-attapulgite modified epoxy acrylate resin.
[0006] Preferably, in step (1), the mass ratio of xylene, nano-attapulgite and γ-aminopropyltriethoxysilane is 3000-6000:100:220-350.
[0007] Preferably, in step (2), the mass ratio of ethanol, amino-attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 1500-4000:100:155-280:25-30.
[0008] Preferably, the reaction temperature in step (2) is 50-70° C., and the reaction time is 4-10 h.
[0009] Preferably, in step (3), the mass ratio of xylene, undecane carboxyl-modified attapulgite, zinc particles and diethylenetriamine is 800-1200:100:0.01-0.06:50-65.
[0010] Preferably, in step (4), the mass ratio of ethanol, imidazoline-grafted attapulgite and benzyl chloride is 1800-5000:100:65-90.
[0011] Preferably, the reaction temperature in step (4) is 50-65° C., and the reaction time is 12-18 h.
[0012] Preferably, in step (5), the mass ratio of butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 120-180:100:14-18:15-20:5-7:4-8:1-6:0.5-1.
[0013] Preferably, the reaction temperature in step (5) is 80-100° C. and the reaction time is 4-8 h.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The quaternary ammonium salt-attapulgite modified epoxy acrylic resin comprises the following steps: firstly, γ-aminopropyltriethoxysilane is used to modify nano-attapulgite to obtain amino-attapulgite; then, in an ethanol solvent, the carboxyl group on the undecane-1,11-dicarboxylic acid reacts with the amine group on the amino-attapulgite under the action of a catalyst, N,N′-dicyclohexylcarbodiamine, to obtain the undecane carboxyl-modified attapulgite; and in a xylene solvent, the undecane carboxyl-modified attapulgite reacts with the amine group on the amino-attapulgite to obtain the undecane carboxyl-modified attapulgite. and diethylenetriamine under the action of catalyst zinc particles, the carboxyl group on the undecanecarboxyl-modified attapulgite and the amine group on the diethylenetriamine undergo amidation reaction, and after the temperature is increased, a cyclization reaction occurs to obtain imidazoline-grafted attapulgite, and in an ethanol solvent, the imidazoline-grafted attapulgite and benzyl chloride undergo quaternization reaction to obtain an attapulgite-grafted corrosion inhibitor, and the obtained attapulgite-grafted corrosion inhibitor is mixed with epoxy resin and acrylic resin to obtain a quaternary ammonium salt-attapulgite-modified epoxy acrylic resin.
[0015] The quaternary ammonium salt-attapulgite modified epoxy acrylic resin is a quaternized imidazoline type corrosion inhibitor. Due to its special structure, it has a stable conformation and low energy, and can show good corrosion inhibition performance when the metal is corroded. The carbon-nitrogen double bond on the imidazoline ring and the lone pair of electrons on the nitrogen atom will have corresponding covalent adsorption with the metal surface, so that the corrosion inhibitor can be adsorbed on the metal surface. After being grafted with attapulgite, the agglomeration of nano-attapulgite is effectively avoided, and it can be evenly dispersed in the matrix. The fine particles of the nano-attapulgite can be filled into the network gaps of the matrix, so that the viscosity of the system is increased, the compatibility between the corrosion inhibitor and the matrix is enhanced, and the acid and alkali resistance of the matrix is effectively adjusted. When coated on the metal, a protective film can be formed on the metal surface to prevent the metal from being corroded and the mechanical properties are improved at the same time. The long-chain alkane chain in the corrosion inhibitor is hydrophobic and can form a hydrophobic layer on the metal surface, effectively hindering the migration of corrosion reactants and effectively promoting the anti-corrosion performance of the compound. The modified coating has excellent corrosion resistance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the synthesis of undecanecarboxyl-modified attapulgite.
[0017] Figure 2 Schematic diagram of the synthesis of imidazoline-grafted attapulgite.
[0018] Figure 3 This is a schematic diagram of the synthesis of attapulgite grafted corrosion inhibitor. DETAILED DESCRIPTION
[0019] To achieve the above object, the present invention provides the following specific implementation methods and examples: A method for preparing a quaternary ammonium salt-attapulgite modified epoxy acrylic resin is as follows: (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 3000-6000:100:220-350 into a reaction container, ultrasonically dispersing, reacting at 80-100° C. for 5-8 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Adding ethanol solvent and amino attapulgite into a reaction container, after ultrasonic dispersion, adding undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 1500-4000:100:155-280:25-30, stirring, reacting at 50-70°C for 4-10 hours, after the reaction is completed, filtering, washing with ethanol and deionized water, and drying to obtain undecane carboxyl modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 800-1200:100:0.01-0.06:50-65 into a reaction container, stirring, heating under reflux, pre-reacting at 130-150° C., reacting for 2-3 hours, raising the temperature, reacting at 180-220° C., reacting for 6-10 hours, ending the reaction, and rotary evaporating to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline grafted attapulgite into a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline grafted attapulgite and benzyl chloride is 1800-5000:100:65-90, stir, react at 50-65° C., and react for 12-18 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 80-100°C for 4-8 hours, and add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane after the reaction. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 120-180:100:14-18:15-20:5-7:4-8:1-6:0.5-1. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin. Example 1
[0020] (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 3000:100:220 into a reaction container, performing ultrasonic dispersion, reacting at 80° C. for 5 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, and the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 1500:100:155:25. Stir and react at 50°C for 4 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl-modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 800:100:0.01:50 into a reaction container, stirring, heating under reflux, and pre-reacting at 130° C. After reacting for 2 hours, raising the temperature and reacting at 180° C. After reacting for 6 hours, the reaction is terminated, and rotary evaporation is performed to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline-grafted attapulgite to a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline-grafted attapulgite and benzyl chloride is 1800:100:65, stir, react at 50°C, and react for 12 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, and react at 80°C for 4 hours. After the reaction, add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 120:100:14:15:5:4:1:0.5. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin. Example 2
[0021] (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 3500:100:250 into a reaction container, performing ultrasonic dispersion, reacting at 85° C. for 6 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, and the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 1800:100:180:26. Stir and react at 55°C for 5 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 900:100:0.02:54 into a reaction container, stirring, heating under reflux, and pre-reacting at 135° C. After reacting for 2.5 hours, raising the temperature and reacting at 190° C. After reacting for 7 hours, the reaction is terminated, and rotary evaporation is performed to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline-grafted attapulgite to a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline-grafted attapulgite and benzyl chloride is 2500:100:70, stir, react at 55°C, and react for 14 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 85°C for 5 hours, and add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane after the reaction. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 130:100:15:16:5.5:4.8:2:0.6. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin. Example 3
[0022] (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 4500:100:280 into a reaction container, performing ultrasonic dispersion, reacting at 90° C. for 6 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, and the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 2800:100:210:27. Stir and react at 60°C for 6 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 950:100:0.03:60 into a reaction container, stirring, heating under reflux, pre-reacting at 140°C, reacting for 2.5 hours, raising the temperature, reacting at 200°C, reacting for 8 hours, ending the reaction, and rotary evaporating to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline-grafted attapulgite to a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline-grafted attapulgite and benzyl chloride is 3800:100:75, stir, react at 55°C, and react for 15 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 90°C for 6 hours. After the reaction, add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 150:100:16.5:17:6.2:6.8:4:0.8. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin. Example 4
[0023] (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 5000:100:320 into a reaction container, performing ultrasonic dispersion, reacting at 95° C. for 7 h, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, wherein the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 3500:100:250:28, stir, react at 65°C, and react for 8 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl-modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 1100:100:0.05:62 into a reaction container, stirring, heating under reflux, and pre-reacting at 145°C. After reacting for 2.5 hours, the temperature was raised and reacted at 210°C. After reacting for 9 hours, the reaction was terminated and rotary evaporated to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline-grafted attapulgite to a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline-grafted attapulgite and benzyl chloride is 4500:100:86, stir, react at 60°C, and react for 16 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 95°C for 7 hours. After the reaction, add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 165:100:17.2:19:6.8:7:5:0.9. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin. Example 5
[0024] (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 6000:100:350 into a reaction container, performing ultrasonic dispersion, reacting at 100° C. for 8 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, and the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 4000:100:280:30. Stir and react at 70°C for 10 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine in a mass ratio of 1200:100:0.06:65 into a reaction container, stirring, heating under reflux, and pre-reacting at 150°C. After reacting for 3 hours, the temperature was increased and reacted at 220°C. After reacting for 10 hours, the reaction was terminated and rotary evaporated to obtain imidazoline grafted attapulgite; (4) Add ethanol solvent and imidazoline-grafted attapulgite to a reaction container, and after uniform ultrasonic dispersion, add benzyl chloride, wherein the mass ratio of the added ethanol, imidazoline-grafted attapulgite and benzyl chloride is 5000:100:90, stir, react at 65°C, and react for 18 hours. After the reaction is completed, perform vacuum distillation, and use a mixed solution of ethanol and acetone for recrystallization to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 100°C for 8 hours, and add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane after the reaction. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 180:100:18:20:7:8:6:1. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin.
[0025] Comparative Example 1 (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane in a mass ratio of 4000:100:300 into a reaction container, performing ultrasonic dispersion, reacting at 90° C. for 6 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) Add ethanol solvent and amino attapulgite into a reaction container, and after ultrasonic dispersion, add undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, and the mass ratio of the added ethanol, amino attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 3000:100:200:28. Stir and react at 60°C for 8 hours. After the reaction is completed, filter, wash with ethanol and deionized water, and dry to obtain undecane carboxyl modified attapulgite; (3) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir in a nitrogen atmosphere, react at 90°C for 6 hours. After the reaction, add undecanecarboxyl-modified attapulgite and defoaming agent polysiloxane. The mass ratio of the added butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, undecanecarboxyl-modified attapulgite and defoaming agent polysiloxane is 150:100:16:18:6:6:4.5:0.8. After mixing evenly, cool and adjust the pH to obtain quaternary ammonium salt-attapulgite modified epoxy acrylic resin.
[0026] The coatings synthesized in the embodiments and comparative examples were poured into a polytetrafluoroethylene mold, shaken, cured at room temperature, and demolded to obtain a flat sample, which was cut into notch-free specimens and subjected to an impact strength test on a JBW-300B simply supported beam impact testing machine to take the corresponding average value.
[0027]
[0028] A standard three-electrode system was used, with a saturated calomel electrode as the reference electrode, a platinum electrode as the auxiliary electrode, a carbon steel test piece uniformly coated with the coating synthesized in the embodiment and the comparative example as the working electrode, and a 5% NaCl solution as the working liquid. The electrochemical test was performed using a CHI660D electrochemical tester at room temperature for 30 days. During the test, the scanning rate of the cathode polarization curve was 0.5 mV / s, and the frequency variation range was 10 -2 -10 5 Hz.
[0029]
Claims
1. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin, characterized in that: The quaternary ammonium salt-attapulgite modified epoxy acrylic resin and the preparation method are as follows: (1) Adding xylene solvent, nano-attapulgite and γ-aminopropyltriethoxysilane into a reaction container, performing ultrasonic dispersion, reacting at 80-100° C. for 5-8 hours, and after the reaction is completed, filtering, washing with ethanol, and drying to obtain amino-attapulgite; (2) adding ethanol solvent and amino-modified attapulgite into a reaction container, and after ultrasonic dispersion, adding undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine, stirring, and reacting. After the reaction is completed, filtering, washing with ethanol and deionized water, and drying to obtain undecane carboxyl-modified attapulgite; (3) Adding xylene solvent, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine into a reaction vessel, stirring, heating under reflux, pre-reacting at 130-150° C., reacting for 2-3 hours, raising the temperature, reacting at 180-220° C., reacting for 6-10 hours, ending the reaction, and rotary evaporating to obtain imidazoline grafted attapulgite; (4) adding ethanol solvent and imidazoline-grafted attapulgite into a reaction container, uniformly dispersing by ultrasonication, adding benzyl chloride, stirring, reacting, and after the reaction is completed, performing vacuum distillation, and performing recrystallization with a mixed solution of ethanol and acetone to obtain an attapulgite-grafted corrosion inhibitor; (5) Add butanol solvent, epoxy resin, methacrylic acid, butyl acrylate, styrene and benzoyl peroxide into a reaction container, stir and react in a nitrogen atmosphere, and after the reaction is completed, add attapulgite grafted corrosion inhibitor and defoaming agent polysiloxane, mix well, cool, and adjust the pH to obtain a quaternary ammonium salt-attapulgite modified epoxy acrylate resin.
2. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: In the step (1), the mass ratio of xylene, nano-attapulgite and γ-aminopropyltriethoxysilane is 3000-6000:100:220-350.
3. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: In the step (2), the mass ratio of ethanol, amino-attapulgite, undecane-1,11-dicarboxylic acid and N,N′-dicyclohexylcarbodiamine is 1500-4000:100:155-280:25-30.
4. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: The reaction temperature in step (2) is 50-70° C. and the reaction time is 4-10 h.
5. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: In the step (3), the mass ratio of xylene, undecane carboxyl modified attapulgite, zinc particles and diethylenetriamine is 800-1200:100:0.01-0.06:50-65.
6. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: In the step (4), the mass ratio of ethanol, imidazoline-grafted attapulgite and benzyl chloride is 1800-5000:100:65-90.
7. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: The reaction temperature in step (4) is 50-65° C. and the reaction time is 12-18 h.
8. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: In the step (5), the mass ratio of butanol, epoxy resin, methacrylic acid, butyl acrylate, styrene, benzoyl peroxide, attapulgite grafted corrosion inhibitor and polysiloxane is 120-180:100:14-18:15-20:5-7:4-8:1-6:0.5-1.
9. A quaternary ammonium salt-attapulgite modified epoxy acrylic resin according to claim 1, characterized in that: The reaction temperature in step (5) is 80-100° C. and the reaction time is 4-8 hours.
Citation Information
Patent Citations
Polysulfide rubber modified anticorrosive sewage-preventing epoxy resin paint
CN1375533A
